IMPLEMENTATION OF ACTIVE LEARNING METHODS IN INCREASING STUDENT INTEREST AND UNDERSTANDING IN HISTORY LESSONS AT SMAN 14 MEDAN - Roberto Simbolon; Arfan Diansyah arfandiansyah; Imelda Megawati Gultom (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to explore and analyze the implementation of active learning methods in increasing students' interest and understanding in history lessons at SMAN 14 Medan. Active learning methods are used as the main approach to presenting historical material to students. Research was conducted by collecting qualitative and quantitative data from students involved in the active learning process. The research results show that the implementation of active learning methods is effective in increasing students' interest in history lessons and increasing their understanding of the material being taught. These findings underline the importance of using interactive and participation-based learning methods to strengthen the learning process in schools. The implications of this research provide a basis for the development of more effective learning strategies in the context of history learning in high schools. However, the implementation of active learning methods depends not only on the type of activity carried out but also on the teacher's pedagogical skills in designing and implementing interactive learning. Therefore, continued support for developing teacher skills in using active learning methods is the key to success in improving the quality of history learning at SMAN 14 Medan. Thus, this research provides a valuable contribution to our understanding of the importance of active learning methods in increasing students' interest in and understanding of history lessons. Continuous efforts are needed to expand the use of these methods and overcome challenges that may arise in their implementation, so as to create more meaningful and valuable learning experiences for students in understanding their historical heritage.